Pengaruh Leadership dan Motivasi Kerja terhadap Kinerja Karyawan di Supermarket Tiara Dewata (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the influence of leadership and work motivation on employee performance at Tiara Dewata Supermarket. The research model used a quantitative descriptive method, and data collection techniques used a questionnaire, using 100 samples. The analytical methods used were multiple linear regression analysis, t-tests, and F-tests to determine the influence of independent variables on the dependent variable. SPSS for Windows version 25 was used for data processing. The results of this study indicate that partially, leadership and work motivation have a positive and significant effect on employee performance, as indicated by values of 0.005 and 0.006, respectively, which are <0.05. Simultaneously, leadership and work motivation have a positive and significant effect on employee performance, with a value of 0.000, which is <0.05. This study recommends that companies pay attention to leadership and work motivation factors to improve employee performance.